2021
DOI: 10.3758/s13423-021-01924-x
|View full text |Cite
|
Sign up to set email alerts
|

Does signal reduction imply predictive coding in models of spoken word recognition?

Abstract: Pervasive behavioral and neural evidence for predictive processing has led to claims that language processing depends upon predictive coding. Formally, predictive coding is a computational mechanism where only deviations from top-down expectations are passed between levels of representation. In many cognitive neuroscience studies, a reduction of signal for expected inputs is taken as being diagnostic of predictive coding. In the present work, we show that despite not explicitly implementing prediction, the TRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In addition, TRACE is proving surprisingly capable of simulating neural level data, including crucial patterns of neural activity hypothesized to be linked to predictive coding. Luthra, Li, You, Brodbeck, and Magnuson (2021) demonstrate that TRACE captures a key pattern observed by Gagnepain, Henson, and Davis (2012) in fMRI: signal reduction when inputs conform to expectations. Brodbeck, Luthra, Gaston, and Magnuson (2021) demonstrate that TRACE captures a complex cross-over interaction observed in representational similarity analyses (Kriegeskorte & Bandettini, 2008) of fMRI (Blank & Davis, 2016) and MEG (Sohoglu & Davis, 2020) data (and demonstrate how this depends crucially on feedback), and also document interesting similarities between MEG studies of speech processing and the sensitivity of different levels of representation in TRACE to information theoretic measures such as surprisal and entropy (and how those relate to specific aspects of TRACE's architecture, such as lateral inhibition and feedback).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In addition, TRACE is proving surprisingly capable of simulating neural level data, including crucial patterns of neural activity hypothesized to be linked to predictive coding. Luthra, Li, You, Brodbeck, and Magnuson (2021) demonstrate that TRACE captures a key pattern observed by Gagnepain, Henson, and Davis (2012) in fMRI: signal reduction when inputs conform to expectations. Brodbeck, Luthra, Gaston, and Magnuson (2021) demonstrate that TRACE captures a complex cross-over interaction observed in representational similarity analyses (Kriegeskorte & Bandettini, 2008) of fMRI (Blank & Davis, 2016) and MEG (Sohoglu & Davis, 2020) data (and demonstrate how this depends crucially on feedback), and also document interesting similarities between MEG studies of speech processing and the sensitivity of different levels of representation in TRACE to information theoretic measures such as surprisal and entropy (and how those relate to specific aspects of TRACE's architecture, such as lateral inhibition and feedback).…”
Section: Discussionmentioning
confidence: 61%
“…4 As such, it is also poised to bridge perceptual, cognitive, and neural studies of language processing. It is obviously useful for researchers interested in making those connections (as we discussed above, TRACE is being used productively to investigate neural data: Brodbeck et al, 2021;Luthra, Li, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To speculate, predictive coding models may account for activity in the N1 in previously tested paradigms without accurately describing the underlying neural processes. For instance, Luthra et al (2021) showed that, in spoken word recognition, interactive activation models may provide an alternative account of the ERP amplitude reduction observed in response to prediction violations, without invoking key features of predictive coding models. Indeed, effects indicative of predictive processing may emerge in a system that that lacks any representations of, or mechanisms implementing, predictions or prediction errors, instead only implementing "pattern completion" (Falandays et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This response reduction is compatible with either a prediction error account (through the suppression of responses tuned to input features that are predicted) or a sharpened signal mechanism (through the suppression of responses tuned away from the input features; for a more detailed explanation, see Introduction and refs. [5,6,19]).…”
Section: Prediction Error Computations During Natural Listeningmentioning
confidence: 99%
“…(19 in the MEG experiment, 21 in the fMRI experiment) were Cambridge Psychology Research Ethics Committee. All were right-handed, native speakers of English, aged between 18 and 40 years and had no self-reported history of hearing impairment or neurological disease.…”
mentioning
confidence: 99%